Critical project delivery strategies for sustainable building construction in South Africa - Chijioke Emmanuel Emere; Clinton Ohis Aigbavboa; Olusegun Aanuoluwapo Oguntona (Frontiers in Built Environment)
Certain practices have been linked with the delivery of projects related to sustainable building construction (SBC). Prior research has underscored the necessity of enhancing SBC project delivery. There have been contentions in the literature regarding the best strategy for successful SBC project delivery. Consequently, this study explored the project delivery strategies (PDS) for SBC in South Africa (SA). The original data was obtained from practitioners in the built environment, primarily in Gauteng province. A quantitative approach was employed with a questionnaire as a data collection tool. The data analysis involved descriptive and inferential statistics, including percentage frequency, mean score, analysis of variance (ANOVA), and principal component analysis (PCA). PCA showcases the key PDS components. Three principal PDS components were identified: sustainable tendering and contracting, integrated project delivery, and sustainable public and private financing. The constituent variables’ factor loadings varied between 0.562 and 0.833. The Cronbach Alpha scores of the components’ measuring variables indicated high reliability and internal consistency exceeding the 0.7 benchmark. The study’s findings are novel and offer PDS insights for SBC project deployment in SA. The analysis uncovered three fundamental project delivery factors for achieving resilient and successful SBC projects. The study recommends prioritising the principal factors. Furthermore, researchers, industry experts, and policymakers can use this study as a roadmap to help them in their coordinated, cooperative, and strategic efforts to identify the critical/principal PDS and establish improvement initiatives to actualise successful SBC project delivery. The study will stir a shift from traditional building approaches to more sustainable, integrated and collaborative project delivery.